ANALYSIS OF THE LABOR MARKET AND ITS INDICATORS - Hasanbekova Zabarjad (Ecomind Press, 2025)
This article analyzes the current state of the labor market in Uzbekistan, the dynamics of employment and unemployment, as well as the share of employment in the informal economy. The article studies statistical indicators for 2024-2025, youth unemployment, migration, and labor market trends. Additionally, the structure of the labor market, the distribution of employment across economic sectors, and the impact of government policy are discussed.
Keywords: Labor market, employment, unemployment, informal employment, labor migration, statistical analysis.